Disorder-enabled hydrodynamics of charge and heat transport in monolayer graphene. (14th May 2019) - Zarenia, Mohammad; Principi, Alessandro; Vignale, Giovanni
Abstract: Hydrodynamic behavior in electronic systems is commonly accepted to be associated with extremely clean samples such that electron–electron collisions dominate and total momentum is conserved. Contrary to this, we show that in monolayer graphene the presence of disorder is essential to enable an unconventional hydrodynamic regime which exists near the charge neutrality point and is characterized by a large enhancement of the Wiedemann–Franz ratio. Although the enhancement becomes more pronounced with decreasing disorder, the very possibility of observing the effect depends crucially on the presence of disorder. We calculate the maximum extrinsic carrier density n c below which the effect becomes manifest, and show that n c vanishes in the limit of zero disorder. For n > n c we predict that the Wiedemann–Franz ratio actually decreases with decreasing disorder. We complete our analysis by presenting a transparent picture of the physical processes that are responsible for the crossover from conventional to disorder-enabled hydrodynamics. Recent experiments on monolayer graphene are discussed and shown to be consistent with this picture.